Effect of Nutrients and Temperature on Growth of Lentinus squarrosulus Mont. LS-BUB-9 - Tantratian, Sumate; Kongpensook, Varapha (Journal of Food Technology, Siam University, 2019)
The mycelia culture of Lentinus squarrosulus Mont. LS-BUB-9 was isolated from a mushroom fruiting body in Ubon Ratchathani Province, Thailand. The culture was grown on a liquid basal medium to reach maximum growth, reaching the stationary phase in 25 days. Concentrations of C-source, N-source in the medium and incubation temperature were the factors investigated. Surface response methodology was used to determine a prediction model for investigating changes of the growth of the culture. The incubation temperature had positive interactions with increasing both N-source and C-source. When increasing incubation temperature from 25 to 35oC, the biomass production increased. The highest biomass production was obtained by incubating at 35oC for 25 days with the addition of 3% (w/v) sucrose and 0.3% (w/v) ammonium sulfate in the basal medium.